CCD UBVI photometry and polarimetry in the open cluster Trumpler 21 - Giorgi, Edgard Ervar Salvador (2001)
CCD UBVI photometry was carried out in the field of the open cluster Trumpler 21. Our data locate the cluster at a distance of 1380 pc in a low absorption zone with E(B-V) = 0.25. The age of the cluster is estimated to be 25-30 × 106 yr based on the superposition of isochrones computed with mass loss and overshooting. The cluster mass spectrum has a slope of 1.44 similar to the typical value 1.35 for field stars. UBVRI polarimetry of its brightest members led us to the finding that diffuse interstellar material is responsible for both polarization percentage and its direction.